The Influence of Revenue Growth and Operating Expenses on Company Value - Amin Hou; Deva Djohan; Duffin; Septa Diana Nabella; Adi Harianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to build a model of insurance company value based on revenue growth and operating expenses with Return on Equity (ROE) as a mediating variable. The study was conducted on six insurance companies listed on the IDX during the period 2020–2024 with a quantitative approach using SEM-PLS. The background of the study is the fluctuation of financial performance, especially the mismatch between revenue growth and equity efficiency and firm value. The results of the analysis show that revenue growth has a significant positive effect on firm value, both directly and through ROE. Conversely, operating expenses have a significant negative effect on firm value and are also mediated by ROE. ROE is proven to be a significant mediating variable in this relationship. The coefficient of determination (R²) value of 0.982 for firm value indicates that the model has a very strong ability to explain the variance of firm value. Meanwhile, R² for ROE of 0.566 indicates a moderate influence of the two independent variables. This study emphasizes the importance of increasing revenue and operational efficiency as a strategy to strengthen firm value and investor confidence.